Investigation into Mechanical Properties and Sliding Wear Behavior of Friction Stir Processed Surface Composite Material. (19th November 2021) - Nattappan, Anbuchezhian; Suganya Priyadharshini, G.; Satish Kumar, T.; Velmurugan, T.; Makeshkumar, M.; Allasi, Haiter Lenin
Abstract : One of the different and pioneering solid-state techniques, friction stir processing (FSP), is employed for the production of surface composites. In this research, the matrix selected was copper-nickel (CuNi) with hard boron carbide particle as reinforcement. The objective of the current research work is to produce reinforced 90/10 copper-nickel surface composites reinforced with B4 C fabricated via FSP. The influence of tool rotational speed on macrostructure, microstructure, grain size analysis, microhardness, and wear studies of friction stir processed (FSPed) CuNi/B4 C surface composites was assessed. For high rotational speed (1400 rpm) of stir tool, the modified surface area found is a maximum of 44.4 mm 2 with uniform dispersion of hard particle reinforcement. The presence of hard particle in the surface area is revealed through the electron imaging and the spectroscopic results. Spectra mapping shows the uniform distribution of hard particle over the FSPed area, and the evidence is obtained with XRD analysis. From the experimentation, it is interesting to report that the reinforcements have decreased the surface hardness for an increased rotational speed of stir tool. The hardness recorded for minimum rotational speed is 223 HV which has gradually decreased to 178 HV for 1300 rpm. It has directly influenced the wear rate of modified FSPed, as hardness is directly proportional to wear behavior. The worn surface and fractured morphology of the CuNi/B4 C surface composites were also studied using Field Emission Scanning Electron Microscope (FESEM).